2009
DOI: 10.1002/jbm.a.32448
|View full text |Cite
|
Sign up to set email alerts
|

Control of proliferation and differentiation of osteoblasts on apatite‐coated poly(vinyl alcohol) hydrogel as an artificial articular cartilage material

Abstract: One of the key challenges in employing biomaterials is determining how to fix them into the surrounding tissue. To enhance the interaction with surrounding bone, amorphous hydroxyapatite (HA) was coated onto the surface of the bio-inert poly(vinyl alcohol) hydrogel (PVA-H), as an artificial cartilage material, by a pulsed laser deposition technique. Next we examined the binding effects of the HA thin film (300 nm thick) to the underlying bone using osteoblast proliferation and differentiation. A mouse osteobla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 51 publications
1
25
0
Order By: Relevance
“…11,13) show that the LCCPCs had no cytotoxic effect on osteoblasts and favorably, their composition and topographical features encourage proliferation of cells. The results is in agreement with literatures that demonstrates enhanced proliferation of osteoblasts on surfaces of HA-containing composites [40,41]. It reveals that the cement component influenced the metabolism of the osteoblasts.…”
Section: Discussionsupporting
confidence: 94%
“…11,13) show that the LCCPCs had no cytotoxic effect on osteoblasts and favorably, their composition and topographical features encourage proliferation of cells. The results is in agreement with literatures that demonstrates enhanced proliferation of osteoblasts on surfaces of HA-containing composites [40,41]. It reveals that the cement component influenced the metabolism of the osteoblasts.…”
Section: Discussionsupporting
confidence: 94%
“…A sustained release of BMP-2 with enhanced cell proliferation and differentiation was achieved. The biomimetic coating obtained in this study was mainly composed of carbonated CaP, an essential inorganic part of hard tissues with osteo-conductive function [30][31][32] . Many studies have demonstrated that apatite coating can facilitate osteogenic differentiation, reduce fibrous encapsulation, and promote bone ingrowth [33][34][35] .…”
Section: Discussionmentioning
confidence: 99%
“…For numbers of applications as implants in the osteo-articular system, both PVA and HA have exhibited good biocompatibility 15 , 22 , 42 , 43 . For PVA/HA composites, previous in vitro studies using different processes and particle sizes have shown that these systems do not cause a strong inflammatory response 44 - 46 and can even induce differentiation and proliferation of osteoblastic cells 6 , 8 , 47 . The prior studies do not demonstrate an optimal size, although we suspect grains on the order of 100 microns will leave pores suitable for osteoblast ingrowth.…”
Section: Discussionmentioning
confidence: 99%
“…For bone prosthetics, coating by osseoconductive ceramics has been shown to significantly improve the strength of the anchorage to bone 6 - 12 . How this approach can be applied to soft tissue substitutes currently motivates strong research efforts 6 - 8 , 13 - 16 . In particular, methods for coatings that contain bioceramics to enhance osseointegration while still adhering properly to the soft implant remains a challenge.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation